2021
DOI: 10.1021/acs.joc.1c00130
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid-Catalyzed Regioselective Koenigs–Knorr-Type Glycosylation

Abstract: Boronic acid-catalyzed regioselective Koenigs− Knorr-type glycosylation is presented. The reaction of an unprotected or partially protected glycosyl acceptor with a glycosyl halide donor in the presence of silver oxide and a low catalytic amount of imidazole-containing boronic acid was found to proceed smoothly, which enables construction of a 1,2-trans glycosidic linkage with high regioselectivities. This is the first example of the use of a boronic acid catalyst to initiate regioselective glycosylation via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Promising results were only obtained when a panel of boronic acids was evaluated as potential co-catalysts (Table 1). While aryl-based boronic acids were more commonly employed as catalysts in cases involving carbohydrate diol complexations 62,63,66 , we observed that in our instance vinylboronic acid performed comparatively much better as a catalyst, while aliphatic boronic acids 22 and 23 were deleterious in the reaction. Density functional theory (DFT) studies (Supplementary Section 'Computational Details') suggested that fine-tuning electron-donating and conjugation effects on the boronate substituent is pivotal to increase nucleophilicity and also to provide stability to the negatively charged boronate resting-state species.…”
Section: Establishment Of the Synergistic Catalysis Methodologymentioning
confidence: 58%
“…Promising results were only obtained when a panel of boronic acids was evaluated as potential co-catalysts (Table 1). While aryl-based boronic acids were more commonly employed as catalysts in cases involving carbohydrate diol complexations 62,63,66 , we observed that in our instance vinylboronic acid performed comparatively much better as a catalyst, while aliphatic boronic acids 22 and 23 were deleterious in the reaction. Density functional theory (DFT) studies (Supplementary Section 'Computational Details') suggested that fine-tuning electron-donating and conjugation effects on the boronate substituent is pivotal to increase nucleophilicity and also to provide stability to the negatively charged boronate resting-state species.…”
Section: Establishment Of the Synergistic Catalysis Methodologymentioning
confidence: 58%
“…31 group that promotes the catalytic active boronate formation by generating an internal B−N dative bond. 32,33 Concurrently, we have reported benzoxaborole (BO) catalysts (Figure 2A). 34 The outstanding cis-1,2-diol affinity of BO 35,36 offers good activity and regioselectivity in the catalyst-controlled modifications of carbohydrates.…”
Section: ■ Introductionmentioning
confidence: 77%
“…The same concept was successfully applied to the Koenigs−Knorr-type glycosylation reaction to enable regioselective glycosylation of nonprotected fucopyranoside and other pyranoside sugars with their 6-OH protected (Figure 13b). 70 Stereoselective formation of the 1,2-cis-α-glycosidic linkage is a challenging task due to nonavailability of neighboring-group participation from a 2-O-acyl protecting group in the glycosyl donor. In 2015, Toshima, Takahashi, and co-workers found that a boronate ester preformed from a glycosyl acceptor worked as a catalyst to promote regioselective 1,2-cis-stereoselective glycosylation reaction with a 1,2-anhydro glycosyl donor (Figure 14a).…”
Section: Boronate Estermentioning
confidence: 99%
“…The observed regioselectivity was explained by the cyclic boronate ester formation with cis -1,2-diol followed by the reaction at the sterically less hindered equatorial hydroxy group. The same concept was successfully applied to the Koenigs–Knorr-type glycosylation reaction to enable regioselective glycosylation of nonprotected fucopyranoside and other pyranoside sugars with their 6-OH protected (Figure b) …”
Section: Covalent Bond-forming Catalysis With 12-diolsmentioning
confidence: 99%